Bridging Language and Technology: Innovating English for Specific Purposes through an Automotive Engineering E-Module - Ningsih, Rahma Pitria; Rosalina, Elsa; Kustini, Siti; Nasrullah, Nasrullah; Umar, Vebrianti (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2025)
The rapid expansion of the global automotive industry requires vocational graduates who are proficient not only in technical skills but also in English, the lingua franca of technology and professional communication. However, many Indonesian vocational students face persistent challenges in mastering discipline-specific English due to the scarcity of contextualized learning materials. To address this gap, the present study employed a Research and Development (R&D) methodology to systematically design, develop, and validate a tailored English for Specific Purposes (ESP) e-module for automotive engineering students at Banjarmasin State Polytechnic. The R&D process consisted of four stages: needs analysis through curriculum review and student questionnaires, design and development of the e-module integrating authentic automotive contexts and multimedia features, pilot implementation with students, and evaluation through expert validation and learner feedback. Expert assessments confirmed the module’s high validity, with scores of 4.7 for linguistic aspects and 4.4 for technical content, while student evaluations emphasized strong relevance (83.3% agreement), accuracy (84.6% agreement), and usability, though language clarity required refinement to accommodate varied proficiency levels. These findings demonstrate that the developed e-module effectively bridges technical and linguistic competencies, enhances learners’ engagement with authentic materials, and strengthens their communicative readiness for professional practice. The study contributes to ESP pedagogy by offering an empirically validated model for integrating technical content with task-based language learning, and its broader implication lies in advancing vocational education to better align with global industry standards in an increasingly digitalized era.